TRADITIONAL USED PLANTS AGAINST COGNITIVE DECLINE - Surve, *Pankaj; Burley, Anil (International Journal of Ayurveda and Pharma Research, 2017)
The medicinal plants in classical literature of Ayurved and traditional folk care health practices provide clues to new area of pharmaceutical research. The numbers of plants had been mentioned in Ayurveda for curing various pathophysiological stages of ailment and these are being practiced in various traditional streams in different parts of India. The present study aims to focus selected herbs that can be beneficial over psychological factors like cognition. Cognitive behavioral performance can be commonly noticed with gradually increasing forgetfulness generally due to old age or some neuropathological factors. It may troublesome or embarrassing to observe such suffering individual with mild behavior problems. But consistent or increasing concern about your mental performance may suggest Cognitive Decline. Ayurveda consider three Gunas i.e., Satva, Raja and Tama along with Tridoshas and their disequilibrium leads to abnormal functioning and behavior pattern of mental health. The significance of mental health is equally empathized under the definition of health by WHO along with physical health. Todays upcoming lifestyle in term of diet and regimen leads to number of Psychological factors. Cognitive Decline is one of them. The selected herbal drugs possess Sadnyastapan property and helpful in cognitive enhancement. Ayurveda mentioned list of plants that are used and practiced for the treatment neurological disorders in traditional indigenous medicine. The medicinal plants possess positive effects on various cognitive functions by means of its multifold action. The selected mentioned drugs in the study can be useful for treatment of neuropsychiatric disorders and capable of enhancing cognitive performance. These herbs can prove better medicaments in case of Cognitive Decline.